Exploring the Nexus Between Mindfulness, Gratitude, and Wellbeing Among Youth With the Mediating Role of Hopefulness: A South Asian Perspective - Ali, Salima Barkat; Ahmad, Munawar Javed; Ramzan, Iqra; Ali, Muhammad; Khan, Kalimullah (Frontiers in Psychology, 2022)
The current study investigates the relationship between mindfulness, gratitude, and psychological well-being of young individuals in Pakistan with the potential role of hopefulness as a mediator between mindfulness, gratitude, and well-being. Data was collected from young individuals (18-40 years old) from Pakistan. A total sample of 500 participants was collected by employing the online survey questionnaire and 374 questionnaires were duly filled and returned. The PLS-SEM technique was used to test the proposed hypotheses. The results of the study found that there is a strong direct relationship between gratitude, mindfulness and, hopefulness, and mindfulness also strongly correlated with well-being. However, the relationship between gratitude and well-being was not statistically significant. Moreover, the mediation results reveal that the relationship between mindfulness, gratitude, and well-being is significantly mediated by hopefulness. This shows that gratitude and mindfulness are crucial in enhancing well-being through hopefulness. The present study is an important contribution to validating the broaden-and-build theory, which suggests hopelessness is a significant factor of a depressive state. It can be indicated that inducing hopefulness could be a significant element of the treatment plan of professional clinical psychologists.